Microbicidal activity of crude extracts from Sargassum wightii against Bacillus cereus (International Current Pharmaceutical Journal, 2014)
The present study was investigated to explore the antibacterial activity of four different solvent (petroleum ether, chloroform, acetone and ethanol) crude extracts of marine brown seaweed Sargassum wightti. Crude extracts were screened against human pathogen Bacillus cereus. The antibacterial efficiency was performed by agar well diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods. The results revealed that the crude extract of petroleum ether showed prominent inhibiting activity against B. cereus and other crude extracts showed below detectable level. The highest microbicidal activity (zone of inhibition) 9.0 ± 0.32 mm was obtained at the concentration of 250 ?g /ml and the lowest activity was 3 ± 0.20 mm at 31.25 ?g /ml concentration. The MIC and MBC values were found to be 125 and 250 ?g /ml respectively. Results of this study suggested that the compounds present in the crude extracts of petroleum ether showed high activity against B. cereus and further studies are required to purify the active principles.DOI: http://dx.doi.org/10.3329/icpj.v3i10.20338 International Current Pharmaceutical Journal, September 2014, 3(10): 326-327